ORGANIC FERTILIZERS ARE EFFECTIVE IN INCREASING GROWTH AND PRODUCTIVITY OF SHALLOT LEMBAH PALU VARIETIES - Bahrudin Bahrudin; Muhammad Ansar; Abdul Rahim Thaha (AGROLAND The Agricultural Sciences Journal (e-Journal), 2019)
Shallot 'lembah palu' variety is the main raw material for fried onion industry in Central Sulawesi. This study aims to examine the LEISA technology package through the use of liquid and solid organic fertilizers from agricultural waste in order to obtain the quality of shallot bulbs that are good as raw material for fried onions. Research using Randomized Complete Block Design (RCBD) was repeated 4 (four) times. Treatment consists of: (A)= without organic fertilizer; (B)= liquid organic fertilizer (Biourin 40 mL/L of water); (C)= solid organic fertilizer (bokashi goat manure 20 ton/ha); (D)= solid organic fertilizer (bokashi goat manure 10 ton/ha) + liquid organic fertilizer (Biourin 20 mL/L of water); (E) = solid organic fertilizer (bokashi goat manure 20 ton/ha) + liquid organic fertilizer (Biourin 40 mL/L of water); (F)= solid organic fertilizer (20 ton/ha bokashi mixture of goat manure and shallot residues); (G)= solid organic fertilizer 20 ton/ha bokashi mixture of goat manure and shallot residues)+liquid organic fertilizer (Biourin 30 mL/L of water); (H)= solid organic 10 ton/ha bokashi mixture of goat manure and shallot residues)+liquid organic fertilizer (Biourin 60 mL/L of water; and (I)= solid organic fertilizer 30 ton/ha bokashi mixture of goat manure and shallot residues)+ liquid organic fertilizer (Biourin 60 mL/L of water). The results of the study were (i) the combination of types and doses of organic fertilizer in general resulted in higher growth and yield of shallots compared to without organic fertilizers, and (ii) a combination of solid organic fertilizer (mixture 20 ton/ha bokashi goat manure and shallot residue), produce number of leaves, leaf dry weight, fresh weight per tuber, and fresh weight of tuber per hectare higher than without organic fertilizer.